Effectiveness of switching from nalfurafine to difelikefalin in patients with hemodialysis-associated pruritus: a prospective interventional study within a new treatment algorithm - Naoko Takahashi; Taku Yoshizawa; Junko Kumagai; Hideki Kawanishi; Shinichiro Tsuchiya; Misaki Moriishi; Takao Masaki (Renal Replacement Therapy)
Abstract Background Since June 2009, our facility has been using an internally developed treatment algorithm that facilitates a comprehensive approach to address each cause of hemodialysis-associated pruritus (HAP), wherein oral nalfurafine, a selective κ-opioid receptor (KOR) agonist, is used for patients resistant to conventional treatments. Upon approval of intravenous difelikefalin, a new KOR agonist, in Japan in December 2023, we revised the treatment algorithm. Here, we evaluate the clinical outcomes of switching patients from nalfurafine to difelikefalin within the new treatment algorithm. Methods Nalfurafine was administered for 6 weeks or longer to 43 patients who were receiving maintenance hemodialysis at our facility in order to treat treatment-resistant HAP in accordance with the treatment algorithm. In 9 of the 43 patients, response to nalfurafine was considered poor on the basis of the presence of moderate or severe daytime or nighttime pruritus according to the Shiratori severity score, or the numerical rating scale (NRS) ≥ 4, despite good adherence confirmed through history-taking. For those nine patients, the medicine was switched to difelikefalin in April 2024 and administered for 16 weeks. The primary endpoint was pruritus severity according to the Shiratori severity score and the NRS. The secondary endpoints were the frequency of itching, presence/absence of pruritus-related insomnia, satisfaction with treatment, and presence/absence of adverse events. Results The numbers of patients with moderate or severe pruritus according to the Shiratori severity score were 4 (44.0%) during the daytime and 6 (66.7%) at nighttime before the change to difelikefalin. However, at week 16 after the change, both had decreased to 0 (0.0%) (p < 0.01 and p < 0.001, respectively). The median [interquartile range] of the NRS was 5 [4, 7] before the change, which significantly decreased to 3 [2, 3] at week 16 after the change (p < 0.005). The number of patients with insomnia due to pruritus was 4 (44.4%) before the change, which significantly decreased to 0 (0.0%) at week 16 after the change (p < 0.01). No adverse events were observed. Conclusions Switching from nalfurafine to difelikefalin appeared to be a useful and safe option for the management of treatment-resistant HAP in patients on hemodialysis.